ID: 98. Issue 1 (November 2015) - Westenius, Veera; Mäkelä, Sanna M.; Julkunen, Ilkka; Österlund, Pamela
<x xml:space="preserve">Abstract</x> The threatening H5N1 and H7N9 avian influenza viruses have infected humans repeatedly with high mortality (30–60%). Most H7N9 or H5N1 virus-infected patients suffer from acute respiratory distress syndrome (ARDS) and severe lower airway inflammation.This raises a question whether the H7N9 virus can induce a similar immune dysregulation as the H5N1 virus, which contributes to the devastating fatal outcome of the disease. We compared the antiviral-inducing mechanisms during the infection with seasonal H3N2 and avian-origin H5N1 and H7N9 influenza viruses in human immune cells. We have previously shown that the novel H7N9 virus, although replicating strongly in human DCs, did not efficiently induce antiviral IFN responses, and this deficiency was associated with a block in IRF3 activation. Interestingly, in H5N1 infection, in spite of the massive IFN induction the expression levels of IFN stimulated genes (ISGs) like MxA and IFITM3 remained relatively low. However, our new studies show that the H5N1 virus induces the robust IFN response by the incoming virus particles even if the virus replication is killed by UV treatment. By killing the H5N1 virus replication we were able to restore the expression of ISGs. Thus we further studied the role of the NS1 protein from different avian influenza viruses in antagonizing the IFN responses. We noticed that NS1 proteins from both H5N1 and H7N9 viruses were able to inhibit IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qfh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> promoter activation. Our data suggests that although both H7N9 and H5N1 avian-origin viruses cause severe pneumonia and ARDS in humans, the underlying mechanisms behind the pathology are distinct.